Stabilization and control of a camera for earth observation in near-space environment - Toh, Si Hui (2015)
There have been an increasing interest in high altitude balloons for novel application in recent years. Both corporate organizations and hobbyists groups are using these balloons to explore and learn more about the near space region for various applications. In this project, it is used in the for Earth observation in near space. For a camera to be stabilized on the craft, a gimbal is used. However, due to tensions caused by the wires running through the gimbal frame, the gimbal movement is obstructed. Hence, a wireless platform is proposed for intra-communication between the gimbal electronics and the flight computer within the near craft. This will ultimately result in a reduction of the rigidity of the gimbal when the number of wires within the gimbal is minimized. Bluetooth technology is explored here. Bluetooth modules, as well as Arduino microcontroller boards will be integrated with the gimbal’s controller board and the camera itself. This allows the user to have greater control over the gimbal’s movements and the camera’s actions. This wireless platform that is to be integrated into the gimbal can be the build-up to a tension-free gimbal system, whereby the gimbal’s controller board is to be integrated with the microcontroller.